University and urban society. A prosopographical database of the Paduan “Studium” in the Middle Ages (1222-1405) - TERENZI, Pierluigi (Studia Universitatis Babeș-Bolyai Historia, 2019)
This article presents and discusses the work and the methodological issues of the project PADU-A (Prosopographical-Access-Database of University-Agenda. Towards a database of students and professors of the first two centuries of the university). The project consists in the realization and exploitation of a prosopographical database, with the aim of producing an advancement in the knowledge of academic population that animated the university of Padua in the years 1222-1405. After having recalled briefly the history of this important Studium, the article firstly presents critically the available sources and the challenges they pose to the researcher and to the realization of a database. Secondly, it illustrates the structure and functioning of the database in connection with the sources’ features. Finally, it presents some research possibilities based upon the data collected and their analysis, with the appropriate methodological approach and precautions. Rezumat: Universitate și societate urbană. O bază de date prosopografică referitoare la “studium”-ul din Padova în evul mediu (1222-1405). Acest material prezintă și discută realizarea și aspectele metodologice asociate proiectului PADU-A (Prosopographical-Access-Database of University-Agenda. Towards a database of students and professors of the first two centuries of the university). Proiectul vizează constituirea și valorificarea unei baze de date de tip prosopografic, care are drept scop o mai bună cunoaștere a “populației academice” care a frecventat și animat Universitatea din Padova între anii 1222-1405. După o prealabilă parcurgere succintă a istoriei acestui important “studium”, articolul de față prezintă în premieră și în manieră critică sursele disponibile și problemele ridicate de acestea atât în raport cu mediul de cercetare, cât și față de construirea bazei de date. În al doilea rând, este ilustrată structura și funcționarea bazei de date în relație cu particularitățile izvoarelor. În cele din urmă, studiul expune câteva perspective de investigație bazate pe datele colectate și pe analiza acestora, având în vedere nu doar abordări metodologice adecvate, ci și o serie de măsuri de precauție. Cuvinte-cheie: Universitate, Padova, studenți, evul mediu, prosopografie, bază de date.